Rachunek kosztów na potrzeby zarządzania strategicznego - Pewniak-Kaliska, Olga (Costs' System for Strategic Management Needs, 2006)
The article concentrates on combining and showing common factors between the costs and the strategy. It points at the piece of information which cost's system can provide with strategic management. The main purpose of the paper is to present The Activity Based Costing and The Value Chain Costing as tools used in the strategic management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 36-43